2020
DOI: 10.3390/nu12113370
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intakes of Zinc, Copper, Magnesium, Calcium, Phosphorus, and Sodium by the General Adult Population Aged 20–50 Years in Shiraz, Iran: A Total Diet Study Approach

Abstract: In the present total diet study, the dietary intake of zinc (Zn), copper (Cu), magnesium (Mg), calcium (Ca), phosphorus (P), and sodium (Na) by healthy adults in Shiraz, Iran, was estimated from the foods as consumed. A total of 580 individual food items were collected, prepared, and pooled into 129 composite samples. The metal concentration was then evaluated using inductively coupled plasma–optical emission spectrometry. The mean intakes of Zn (12.92 mg/d), Cu (3.80 mg/d), and Mg (412.68 mg/d) exceeded the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Two authors (JL and DHC) independently extracted the following data from eligible studies: (1) first author and publication year, (2) population, (3) the number of cases and participants in each study, (4) category of exposure (dietary and supplementary zinc), (5) outcome, (6) the estimated summary effect (ES, MD, OR, RR, SMD, and WMD), (7) corresponding 95% confidence intervals (CIs), (8) the number of included studies, (9) study design (cohort, case-control, cross-sectional and RCT), (10) type of comparisons (<20 mg/day Vs. never, >20 mg/day vs. never, highest vs. lowest and increment of 5 mg or 100 mg of dietary or supplementary zinc), (11) effect model (fixed or random), (12) I 2 statistic value, (13) Cochran's Q test P-value, (14) Egger's test P value. If more than one outcome was reported in one article, we extracted each outcome respectively.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two authors (JL and DHC) independently extracted the following data from eligible studies: (1) first author and publication year, (2) population, (3) the number of cases and participants in each study, (4) category of exposure (dietary and supplementary zinc), (5) outcome, (6) the estimated summary effect (ES, MD, OR, RR, SMD, and WMD), (7) corresponding 95% confidence intervals (CIs), (8) the number of included studies, (9) study design (cohort, case-control, cross-sectional and RCT), (10) type of comparisons (<20 mg/day Vs. never, >20 mg/day vs. never, highest vs. lowest and increment of 5 mg or 100 mg of dietary or supplementary zinc), (11) effect model (fixed or random), (12) I 2 statistic value, (13) Cochran's Q test P-value, (14) Egger's test P value. If more than one outcome was reported in one article, we extracted each outcome respectively.…”
Section: Data Extractionmentioning
confidence: 99%
“…Furthermore, zinc therapy is to some certain extent applied in clinical treatment and prevention of COVID-19 (10), which further proved the importance of zinc. Zinc is distributed in a wide range of food, including meat (fish, red meat, and meat products), grains, cereals, dairy products, and dietary supplements (11). Apart from exogenous zinc, there might be several potential endogenous zinc-preserving organs: pancreas, hepatobiliary, gastroduodenal epithelium, and other possible sites (12).…”
Section: Introductionmentioning
confidence: 99%
“…Few countries such as Iran, Jordan, KSA, Kuwait, and the UAE have further expanded their food reformulation interventions to other food products, including dairy, salty snacks, processed meat, etc. This is encouraging given that studies conducted in EMR countries have identified important contributors to salt, other than bread, including cereals and cereal products [ 103 ], dairy [ 103 , 193 ], prepared meals [ 58 ], salted foods [ 193 ], and processed meats [ 193 ].…”
Section: Discussionmentioning
confidence: 93%
“…Data regarding the baseline levels of salt/sodium in specific foods or meals were collected in 16 countries of the EMR (73%), including Bahrain, Egypt, Iran, Iraq, Jordan, KSA, Kuwait, Lebanon, Morocco, Oman, Pakistan, Palestine, Qatar, Tunisia, UAE, and Yemen [ 27 , 28 , 43 , 53 , 69 , 84 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 ]. These salt/sodium content data were collected based on food composition databases, food analysis, or industry self-reporting.…”
Section: Resultsmentioning
confidence: 99%
“…Copper (Cu) is an indispensable micronutrient for humans and animals (Babaali et al, 2020;Bost et al, 2016;Chen et al, 2020). The metal is required for numerous physiological and biochemical processes and functions.…”
Section: Introductionmentioning
confidence: 99%